2015
DOI: 10.11124/jbisrir-2015-2307
|View full text |Cite
|
Sign up to set email alerts
|

Safe storage time for reprocessed flexible endoscopes: a systematic review

Abstract: Endoscopes can be stored for seven days if they have been effectively reprocessed and appropriately stored. Ongoing surveillance cultures are necessary to verify reprocessing effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
6
0
2
Order By: Relevance
“…2 Results of a systematic review showed that the average time for flexible endoscope storage ranged from 2 to 56 days. 12 Microbial growth was seen in 2% of endoscopes that were stored for at least three days and in 4% of endoscopes that were stored for at least seven days. The reviewers recommended that storage of reprocessed flexible endoscopes (ie, gastroscopes, colonoscopes, and duodenoscopes) not exceed seven days.…”
Section: Storagementioning
confidence: 99%
See 1 more Smart Citation
“…2 Results of a systematic review showed that the average time for flexible endoscope storage ranged from 2 to 56 days. 12 Microbial growth was seen in 2% of endoscopes that were stored for at least three days and in 4% of endoscopes that were stored for at least seven days. The reviewers recommended that storage of reprocessed flexible endoscopes (ie, gastroscopes, colonoscopes, and duodenoscopes) not exceed seven days.…”
Section: Storagementioning
confidence: 99%
“…The reviewers recommended that storage of reprocessed flexible endoscopes (ie, gastroscopes, colonoscopes, and duodenoscopes) not exceed seven days. 12 The interdisciplinary team should determine the maximum storage time; in addition, they should establish a process that allows personnel to easily recognize when an endoscope has exceeded its maximum storage time and reprocess it before use. 2 Flexible endoscope storage cabinets should be cleaned with an Environmental Protection Agency-registered dis infectant regularly and when soil is visible.…”
Section: Storagementioning
confidence: 99%
“…Die breite Spanne an Studiendesigns führt zu sehr unterschiedlichen Ergebnissen und Empfehlungen zu Lagerungszeiten. In einem systematischen Review von Schmelzer et al [10] zum Beispiel bemängeln die Autoren in den gesammelten Studien zu kleine Stichproben mit zu wenigen Endoskopen.…”
Section: Zielunclassified
“…A practical benefit of the use of forced-air drying cabinets is the extended time that instruments can be used for a procedure without the need for reprocessing. Schmelzer et al 58 summarized the proportion of contaminated endoscopes, defined as the presence of any pathogen and >10 CFU/mL in seven studies that sampled all channels for length of time and type of storage. Drawing from these data, it is considered safe to use an endoscopic instrument for a period of 7 days without the need for pre-procedure reprocessing.…”
Section: Instrument Reprocessing and Environmental Managementmentioning
confidence: 99%